Temperature-controlled growth of ZnO Thin films by spray pyrolysis: Influence on physical properties for photovoltaic applications - Ako, Ognanmi; Baneto, Mazabalo; Gboglo, Alphonse Déssoudji; Senthilkumar, Muthusamy; Haris, Muthiah (Edelweiss Applied Science and Technology, 2025)
This work investigates the influence of deposition temperature on the structural, morphological, and optical properties of zinc oxide (ZnO) thin films synthesized by spray pyrolysis. Films were deposited at 300 °C, 350 °C, and 400 °C using a 0.3 M zinc acetate precursor solution, followed by annealing at 400 °C for 3 hours. X-ray diffraction revealed that all films are polycrystalline with a hexagonal wurtzite structure, exhibiting a preferred (002) orientation that becomes more pronounced at higher deposition temperatures. Fourier-transform infrared spectroscopy confirmed the presence of characteristic Zn–O vibrations and surface functional groups. Scanning electron microscopy showed uniform and dense film coverage, with a distinct change in morphology from aggregated nanocrystals at 300 °C to microplates and nanograins at 350 °C and 400 °C. UV-visible spectroscopy indicated an increase in optical transmittance with temperature, reaching up to 85% at 400 °C in the visible range. The optical band gap slightly increased with deposition temperature, ranging from 3.26 eV to 3.28 eV. Based on the structural, morphological, and optical properties, 400 °C is identified as the optimal deposition temperature for ZnO thin films, offering enhanced crystallinity, surface quality, and optical transparency essential for improving the performance of photovoltaic devices.